Redescription of the Oriental lace-bug Recaredus rex Distant, 1909 (Hemiptera: Tingidae: Tinginae), and its new tribal assignment, with a key to Ypsotingini - Lis, Barbara; Parveen, Shama; Ramamurthy, Vilayanoor Venkataraman (Zootaxa, 2013)
One of the most enigmatic lace bug genera, Recaredus, was described by Distant (1909) from West Bengal in India. In its description, the author suggested (p. 361) that “this genus apart from the structure of the head has a considerable resemblance to Acalypta Westw., a Palaearctic genus; in the Indian enumeration it may be placed after Phatnoma and probably requires a divisional separation.”